12‐month longitudinal cognitive functioning in patients recently diagnosed with bipolar disorder. (25th November 2013) - Torres, Ivan J; Kozicky, Jan; Popuri, Swetha; Bond, David J; Honer, William G; Lam, Raymond W; Yatham, Lakshmi N
<x xml:space="preserve">Abstract</x> Objectives Although cognitive deficits are observed in the early stages of bipolar disorder, the longitudinal course of neuropsychological functioning during this period is unknown. Such knowledge could provide etiologic clues into the cognitive deficits associated with the illness, and could inform early treatment interventions. The purpose of the present study was to evaluate cognitive change in bipolar disorder in the first year after the initial manic episode. Methods From an initial pool of 65 newly diagnosed patients with bipolar disorder (within three months of the end of the first manic or mixed episode) and 36 demographically similar healthy participants, 42 patients [mean age 22.9 years, standard deviation (SD) = 4.0] and 23 healthy participants [mean age 22.9 years (SD = 4.9)] completed baseline, six‐month, and one‐year neuropsychological assessments of multiple domains including processing speed, attention, verbal and nonverbal memory, working memory, and executive function. Patients also received clinical assessments, including mood ratings. Results Although patients showed consistently poorer cognitive performance than healthy individuals in most cognitive domains, patients showed a linear improvement over time in processing speed (p = 0.008) and executive function (p = 0.004) relative to the comparison group. Among patients, those without a history of alcohol/substance abuse or who were taken off an antipsychotic treatment during the study showed better improvement. Conclusions The early course of cognitive functioning in bipolar disorder is likely influenced by multiple factors. Nevertheless, patients with bipolar disorder showed select cognitive improvements in the first year after resolution of their initial manic episode. Several clinical variables were associated with better recovery, including absence of substance abuse and discontinuation of antipsychotic treatment during the study. These and other factors require further investigation to better understand their contributions to longitudinal cognitive functioning in early bipolar disorder.